2011
DOI: 10.4065/mcp.2010.0600
|View full text |Cite
|
Sign up to set email alerts
|

26-Year-Old Man With Recurrent Urinary Tract Infections

Abstract: A 26-year-old male college student presented with 1 week of constant, right lower quadrant, throbbing abdominal pain that was worse after eating and accompanied by bilious emesis. He had experienced similar, albeit less severe and self-limited, episodes of abdominal pain during the preceding 6 months. He denied fevers or chills but had lost 4.5 kg (10 lbs) in the past 6 months. During the same time period, he was treated twice with antibiotics for urinary tract infections (UTIs) after reporting symptoms of dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In our case, we report the occurrence of symptomatic lower UTI in a diabetic man with an enlarged prostate caused by an unusual pathogen in humans, E. hirae. Clinical diagnosis of our patient showed that the infection was limited to the lower urinary tract based on the absence of clinical signs related to upper UTI, such as flank pain, vomiting and nausea [4] , and to prostatitis, such as prostate pain, fever, chills, body aches and perineal pain [5,8] . Notably, in addition to prostate enlargement, urinary tract instrumentation, infection with HIV, interventions of the male urogenital tract and underlying illnesses, such as diabetes, are the main predisposing risk factors for UTI in men [8,9] .…”
Section: Discussionmentioning
confidence: 84%
“…In our case, we report the occurrence of symptomatic lower UTI in a diabetic man with an enlarged prostate caused by an unusual pathogen in humans, E. hirae. Clinical diagnosis of our patient showed that the infection was limited to the lower urinary tract based on the absence of clinical signs related to upper UTI, such as flank pain, vomiting and nausea [4] , and to prostatitis, such as prostate pain, fever, chills, body aches and perineal pain [5,8] . Notably, in addition to prostate enlargement, urinary tract instrumentation, infection with HIV, interventions of the male urogenital tract and underlying illnesses, such as diabetes, are the main predisposing risk factors for UTI in men [8,9] .…”
Section: Discussionmentioning
confidence: 84%
“…Recurrent UTI in men warrants evaluation for structural abnormalities, colovesical fistulas associated with colonic malignancy or IBD, enlarged prostate, and unprotected sexual intercourse. Screening for immunologic disorders that might increase the risk of infection with the human immunodeficiency virus and hematologic malignancies is also recommended [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, organisms such as Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, or Ureaplasma urealyticum are typically STIs. Yeast infections suggest underlying immunosuppression that occurs with diabetes or corticosteroid use [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations